2021
DOI: 10.3390/pharmacy9030116
|View full text |Cite
|
Sign up to set email alerts
|

Transferring Key Success Factors from Ambulatory Care into the Community Pharmacy in the United States

Abstract: In the United States, pharmacists’ scope of practice continues to expand, with increasing opportunities for pharmacists in all practice settings to enhance health in society. In ambulatory care, pharmacists remain integral members on the healthcare team and have demonstrated positive impacts on patient care. Sharing similar characteristics as pharmacists in the community setting, a deeper look into common elements of a successful ambulatory care practice that can be applied in the community pharmacy setting is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“… 41 Previous studies have also shown that the professional level of pharmacists affects the satisfaction of patients in PMC, 12 and patients have a high demand for pharmacists in PMC with extensive pharmaceutical knowledge, experience in the use of medication and communication skills. 42 Pharmacist’s unique knowledge base and skill were considered to be elements of a successful ambulatory care practice in America 43 and determinants of willingness to pay for the pharmaceutical care in Saudi Arabia. 44 One reason for this strong preference for pharmacists’ competence may be that in practice, only 10.03% of hospitals in China have PMCs, and PMCs are new to most of the respondents.…”
Section: Discussionmentioning
confidence: 99%
“… 41 Previous studies have also shown that the professional level of pharmacists affects the satisfaction of patients in PMC, 12 and patients have a high demand for pharmacists in PMC with extensive pharmaceutical knowledge, experience in the use of medication and communication skills. 42 Pharmacist’s unique knowledge base and skill were considered to be elements of a successful ambulatory care practice in America 43 and determinants of willingness to pay for the pharmaceutical care in Saudi Arabia. 44 One reason for this strong preference for pharmacists’ competence may be that in practice, only 10.03% of hospitals in China have PMCs, and PMCs are new to most of the respondents.…”
Section: Discussionmentioning
confidence: 99%